GASTRIC EMPTYING SCINTIGRAPHY IN ASSESSMENT OF CHRONIC VOMITING - Jielani, Asif; Hussain, Jawad Akhtar; Rasheed, Rashid (Journal of Ayub Medical College Abbottabad, 2018)
Gastroparesis being multifocal abnormality is characterized by objective feeling of prolong time of gastric retention without any evidence of anatomical blockage. The key symptoms include early satiety, feeling of fullness after meals, nausea, vomiting, bloating, and upper abdominal pain. Radio isotopic Gastric emptying study using radiolabelled test food is integrated clinically for evaluation of functional gastric motility disorders. We present a young female having abdominal pain and vomiting for two months. She was investigated for anatomical causes and no abnormality was uncovered. Gastric Emptying scintigraphy revealed delayed lag phase and half gastric emptying time consistent with the diagnosis of Gastroparesis. Keywords: Gastroparesis; Gastric Emptying Scintigraphy; lag phase; quantitative